Musik Salating sebagai Wujud Kreativitas Kelompok Kuarsa Mahakam di Kota Samarinda - Zenita, Rifkia; Pratama, Zamrud Whidas; Setyoko, Aris (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2023)
This study aims to describe the presentation form of Salating music and the creativity of the Kurasa Mahakam group. The method used is qualitative with a descriptive analysis approach. The method used is qualitative with a descriptive analysis approach. The research steps include determining the research location and data collection techniques (literature study, observation, interviews, documentation), and laboratory work. The results of this study show that the creativity of the Kurasa Mahakam group is built from the 4P aspects, which include person, process, press, and product. The person includes all members of the Kurasa Mahakam group. The process starts from (a) the emergence of anxiety from within each member of the Kurasa Mahakam group towards the sustainability of traditional music in Samarinda City, (b) seeking inspiration by conducting discussions, (c) getting ideas and solutions by establishing the Kurasa Mahakam group, to (d) producing a creative product. The pressures of the Kurasa Mahakam group come from within each member and the external environment. The creative product of the Kurasa Mahakam group is Salating music.